Analisis Keabsahan Administratif Persetujuan Lingkungan Proyek Pltu Teluk Sepang Pasca Undang-Undang Cipta Kerja - Wulandari .; Muhammad Daffa Ananda; Naisyah Zahra Maulidiyah; Rendy Agung Kurniawan; Divana Pramesury (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study aims to analyze the administrative validity of the environmental approval for the Teluk Sepang Steam Power Plant (PLTU) project following the enactment of Law Number 11 of 2020 concerning Job Creation and to examine the application of the principles of authority, procedure, substance, and the General Principles of Good Governance (AUPB) in its issuance. This study also discusses legal protection for affected communities in environmental approval disputes at the State Administrative Court (PTUN). The research uses a normative legal research method with statutory, case, and conceptual approaches. Legal materials consist of primary, secondary, and tertiary legal sources obtained through library research and analyzed descriptively and qualitatively. The results show that the transition from environmental permits to environmental approvals under the Job Creation Law and the risk-based licensing system has changed the mechanism of environmental administrative supervision. In the Teluk Sepang PLTU case, the environmental approval was formally issued by authorized officials and in accordance with administrative procedures; however, substantively there are still weaknesses regarding environmental protection, public participation, transparency, and the application of the precautionary principle. Therefore, stronger administrative supervision and public participation are needed to achieve a balance between economic development and ecological justice.